2013
DOI: 10.5114/ceji.2013.39763
|View full text |Cite
|
Sign up to set email alerts
|

Association study between polymorphism of interleukin 12B 1188A/C and hepatitis B virus infection in a Chinese Han population

Abstract: Background: several studies demonstrated that the genetic factor contributes a lot to the etiology of 1.976, p = 0.372, df = 2, and for alleles, p = 0.623, oR = 0.959,.Conclusions: our results indicated that the il-12B1188 a/C polymorphism was not associated with the development of HBV infection in the Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…However, these allele frequencies did not show any statistical significance. A study has also reported similar results as their study reported no significant association between the allele frequencies and incidences of HBV infections in the Han Chinese population [59].…”
Section: Discussionsupporting
confidence: 65%
“…However, these allele frequencies did not show any statistical significance. A study has also reported similar results as their study reported no significant association between the allele frequencies and incidences of HBV infections in the Han Chinese population [59].…”
Section: Discussionsupporting
confidence: 65%